2018
DOI: 10.1186/s13013-018-0173-z
|View full text |Cite
|
Sign up to set email alerts
|

Truncal changes in children with mild limb length inequality: a surface topography study

Abstract: BackgroundLimb length Inequality (LLI) in children and adults may affect posture, gait, and several truncal parameters, and it can cause spinal scoliosis. In literature, however, there is a paucity of assessment of truncal and spinal changes due to mild LLI in children. This report presents children with LLI, and it aims to provide information in pelvic imbalance, spinal posture, and scoliotic curve, using surface topography analysis which is a novel methodological approach for this condition.Study designThis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…There are different types of LLD and scoliosis. LLD can be subdivided into two groups, structural LLD, when there is structural shortening of lower extremity in one side, and functional LLD, which is a result of altered biomechanics of the lower extremity including the pelvis 13) . Likewise, scoliosis can be divided into structural and functional scoliosis, both of which have different biomechanical characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are different types of LLD and scoliosis. LLD can be subdivided into two groups, structural LLD, when there is structural shortening of lower extremity in one side, and functional LLD, which is a result of altered biomechanics of the lower extremity including the pelvis 13) . Likewise, scoliosis can be divided into structural and functional scoliosis, both of which have different biomechanical characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found that LLD is correlated with pelvic tilt in the coronal plane, also called pelvic obliquity 1,2,13,14,[16][17][18] . Some have studied the immediate effects of artificially induced LLDs, using different measuring techniques and showed that LLD affected the pelvic disposition creating pelvic obliquity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The kind of measurement that we proposed was conducted for the first time, so there is no strict comparison with other research. The most common gait analysis is conducted in children with scoliosis or cerebral palsy (CP) or in adults with hemiplegia [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. We have tried to compare some of the results, while keeping cautions.…”
Section: Discussionmentioning
confidence: 99%